2015
DOI: 10.1007/s00265-015-1977-y
|View full text |Cite
|
Sign up to set email alerts
|

Territoriality in a snake

Abstract: Territorial behaviour, whereby dominant animals gain priority access to critical resources, is widespread in some animal lineages, but rare in others. Theory suggests that territoriality will evolve only when animals can economically defend sites that contain critical resources (typically mates, sometimes food). In striking contrast to their close relatives the lizards, male defence of territories for access to mates has not been reported in snakes. In south-eastern Australia, receptive female small-eyed snake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Male European Adders Vipera berus sometimes remain close to their female partners for a few days post-mating (Madsen and Shine 1993b;Luiselli 1995), and male rattlesnakes Crotalus viridis have been reported to lie on top of females -but again, only briefly et al 1994). In Australia, male Small-eyed Snakes Cryptophis nigrescens defend thermally optimal rocky shelters that attract females, battling other males that approach; and hence, this behaviour may give the territory-holder exclusive mating access to females using that shelter-site (Webb et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male European Adders Vipera berus sometimes remain close to their female partners for a few days post-mating (Madsen and Shine 1993b;Luiselli 1995), and male rattlesnakes Crotalus viridis have been reported to lie on top of females -but again, only briefly et al 1994). In Australia, male Small-eyed Snakes Cryptophis nigrescens defend thermally optimal rocky shelters that attract females, battling other males that approach; and hence, this behaviour may give the territory-holder exclusive mating access to females using that shelter-site (Webb et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our understanding of mating systems in snakes is based primarily on studies of natricine colubrids that court and mate in large aggregations in Europe and North America (e.g., Madsen and Shine 1993a;Luiselli 1995;Shine 2012) and viperid snakes from the same two continents (e.g., Madsen and Shine 1993b;Duvall and Schuett 1997). Far less research has been directed towards snakes from other lineages, living in other parts of the world (Shine 2003; but see Webb et al 2015). The most intensively-studied Australian species in this respect is the Carpet Python Morelia spilota, a large (to 3 m, 7 kg) pythonid species with a wide but fragmented distribution across continental Australia (Cogger 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Males often compete for females and therefore defend resources that females need for reproduction such as breeding sites (Emlen & Oring, 1977). When some males are stronger than others they can gain priority access to clumped resources and thereby increase their probability for mating with multiple females (mammals: Clutton-Brock, 1989; reptiles: Webb, Scott, Whiting, & Shine, 2015;Halliwell, Uller, Wapstra, & While, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have reported extensive home range overlap but conspecific avoidance at the scale of specific shelters [ 23 , 24 ]. However, active defense of and conspecific exclusion from an area (i.e., territoriality) [ 9 ] appears very rare in snakes [ 25 , 26 , 27 , 28 ]. Indeed, many species of snakes show very dense conspecific aggregations [ 25 ] yet these aggregations often occur near high concentrations of resources such as communal hibernacula, gestation sites, distinct habitats (e.g., wetlands or riparian habitats), cover objects, prey, or potential mates [ 25 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many species of snakes show very dense conspecific aggregations [ 25 ] yet these aggregations often occur near high concentrations of resources such as communal hibernacula, gestation sites, distinct habitats (e.g., wetlands or riparian habitats), cover objects, prey, or potential mates [ 25 , 29 , 30 , 31 ]. In such cases, the benefits and efficacy of maintaining exclusive access to those resources may be far below the costs [ 32 ] although the only two studies demonstrating territorial behavior in snakes both involved spatially clustered resources, i.e., sea turtle nests [ 27 ] and shelter sites [ 28 ]. Excluding individuals from an area where resources are widely dispersed may prove similarly uneconomical.…”
Section: Introductionmentioning
confidence: 99%